Microgrid planning and design under uncertainty: A case study in Northern Angola - Kamanzi, Brian (Department of Electrical Engineering, 2020)
The national energy development plan for Angola, Angola Energia 2025, identifies the need to balance efforts to expand access to electricity in countries with low levels of industrialisation, across the urban and rural spheres. This need is coupled with the urgency of investing in environmentally sustainable technologies responding to local and international targets addressing the impacts of Climate Change. This dissertation seeks to assess the feasibility of an electricity micro-grid system (a) for uplifting the quality of life and development of two neighboring Angolan coastal villages, and (b) one that (I) depends entirely on domestic renewable sources of electricity generation; (ii)has a sustainable initial generating capacity of not less than 2MW and (iii) is flexible enough to undergo future expansion as needed over time. The design of a proposed Microgrid solution for N'zeto and Tomboco villages located in Angola is developed through a thorough context study used in conjunction with remotely acquired contextual data and a variety of estimation and model techniques. Microgrids are defined as a group of interconnected loads and distributed energy resources within clearly defined electrical boundaries that acts as a single controllable entity functioning with two modes of operation. The Microgrid design process requires a set of context specific empirical data ranging from load profiles of the site under survey to the availability of endogenous energy resources. The existence of documented public policy, the domestic availability of renewable resources in and around the study area, the present low population density in rural Angola, the low level of Angola's rural electrification , and the existence of financing mechanisms which the country can afford. The load profile and contemplated electrical energy consumption in the study area along with an estimation of the availability, nature, diversity, and extent of the domestic renewable energy sources are developed as key inputs for design decisions related to component sizing. A comparative evaluation of their performance of two proposed candidate solutions, derived from the assessment of the available energy resources is used as a basis to select preferred candidate. The proposed solution is subjected a sensitivity analysis of key design variables. Aspects of the selected design, including concept of operations, reticulation and a discussion on the possible downstream benefits are elaborated in compliance with the technical and policy constraints of the proposed electrification scheme.